A Phenomenological Experience of Sound: Notes on Francisco López. Issue 1 (4th March 2019) - Solomos, Makis
Abstract : This article provides an overview of the output of sound artist Francisco López (b. Madrid, 1964) by examining his music (or soundworks), his writings, and his performances. Unlike electroacoustic music, which develops its own sound material, López's works chiefly stem from field recordings. However, we are not dealing with documentation or soundscape compositions here: while the origin of the sounds is often recognisable, the emphasis tends to be on immersion inside the sound-in-itself. Such autonomization of sound nullifies the representational level and tries to open listening—which is pivotal for López, who in his performances seeks 'profound listening'—to a phenomenological experience of sound.